Distribution, input pathway and mass inventory of black carbon in sediments of the Gulf of Thailand, SE Asia. (5th March 2016) - Hu, Limin; Shi, Xuefa; Bai, Yazhi; Fang, Yin; Chen, Yingjun; Qiao, Shuqing; Liu, Shengfa; Yang, Gang; Kornkanitnan, Narumol; Khokiattiwong, Somkiat
Abstract: The coastal margins around Southeast Asia (SE Asia) may serve as an ideal location to study the source-sink process of sedimentary black carbon (BC) because SE Asia has been identified as one of the major BC emission source regions in the world. This study provides an extensive picture of recent regional-scale sedimentary BC sequestration in the Gulf of Thailand (GOT), a tropical marine system in SE Asia. Generally, the sedimentary BC concentrations (0.07–3.99 mg/g) were in the low to moderate ranges of those obtained in other coastal sediments around the world. Regional variability of the BC and its correlation with the sediment grain size and total organic carbon (TOC) content indicated a general hydrodynamic constraint on BC occurrence in the lower Gulf in contrast to the upper Gulf with a more source dependence due to the direct land-based input. BC/TOC% values and the varied BC components (char and soot), as well as their correlations suggested that char was the predominant constituents of sedimentary BC both in the upper and lower Gulf, which could be mainly derived from biomass burning and entered into the nearshore region through direct fluvial transport and surface run-off. The estimated BC burial flux (∼212 μg/cm 2 /y) and mass inventory (∼200 Gg/y) in the GOT on the hundred-year timescale were of the same order of magnitude compared with other oceanic margins, and thus the tropical shelf sediments from SE Asia could serve as an important sink of land-emitted BC. Highlights: Occurrence of the sedimentary BC was firstly examined in the GOT, a tropical shelf regime. Char was the predominant constituents of sedimentary BC both in the upper and lower Gulf. The tropical shelf from SE Asia served as an important depository of the land-emitted BC.